Anti-money laundering: external accountants as “gate-keepers” in money laundering schemes in Latvia - Reinberga, Krista Zinaīda (Riga Graduate School of Law, 2019)
The main aim of the master’s thesis is to present an analysis of accountants’ involvement in money laundering schemes due to the lack of regulation on the profession. The research is based on the Financial Action Task Force (FATF) recommendations, different non-financial sector players and EU Member State policy comparison on accounting profession matters.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Financial law; Money laundering; Latvia